2021
DOI: 10.1001/jamadermatol.2020.5731
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatizing Alopecia—Perspectives of a Bald Dermatologist

Abstract: Kimball AB, Sobell JM, Zouboulis CC, et al. HiSCR (Hidradenitis Suppurativa Clinical Response): a novel clinical endpoint to evaluate therapeutic outcomes in patients with hidradenitis suppurativa from the placebo-controlled portion of a phase 2 adalimumab study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This and other studies have demonstrated that hair loss is psychosocially burdensome to patients and time‐consuming and difficult to hide 9,16–22 . Patients have demonstrated proficiency in assessing their own hair loss and informed that near‐complete scalp hair regrowth (≤ 20% missing hair/SALT score ≤ 20) would restore a sense of normality 28,33,36 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This and other studies have demonstrated that hair loss is psychosocially burdensome to patients and time‐consuming and difficult to hide 9,16–22 . Patients have demonstrated proficiency in assessing their own hair loss and informed that near‐complete scalp hair regrowth (≤ 20% missing hair/SALT score ≤ 20) would restore a sense of normality 28,33,36 .…”
Section: Discussionmentioning
confidence: 90%
“…This and other studies have demonstrated that hair loss is psychosocially burdensome to patients and time-consuming and difficult to hide. 9,[16][17][18][19][20][21][22] Patients have demonstrated proficiency in assessing their own hair loss and informed that near-complete scalp hair regrowth (≤ 20% missing hair/SALT score ≤ 20) would restore a sense of normality. 28,33,36 Therefore, it is not only feasible but critically important to assess the clinical signs of AA, including scalp hair loss, from the patient perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Most skin diseases are potentially stigmatizing because they are visible. [7] Yet skin diseases, especially hair loss, are often deemed cosmetic, leading to undertreatment by clinicians and substantial psychological and financial burdens. The skin diseases considered stigmatizing are mostly leprosy, alopecia, vitiligo, and others visible.…”
mentioning
confidence: 99%